Memahami Cara Belajar dan Kesulitan Siswa dalam Menyelesaikan Soal Pola Bilangan - Adelia Indriani; Zahwah Zahwah; Syutaridho Syutaridho (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
This research aims to examine the learning methods and challenges faced by several students when solving mathematics problems regarding number patterns, with an emphasis on analyzing students' thinking processes. This study employs an approach to analyze students' ways of thinking. In this study, a qualitative approach is used with a case study method on a group of junior high school students. Information was collected through observations and analysis of students' work. The findings of the research indicate that students apply various strategies in understanding the material of number patterns, which include memorizing patterns to trying to find their own formulas. However, many students face difficulties in drawing conclusions about patterns and connecting relevant mathematical concepts to everyday life. Common mistakes include errors in recognizing patterns, errors in calculations, and a lack of precision in understanding problems. Analysis of the thinking process shows that some students are still at the concrete operational thinking level, so they need visual aids and real-life examples to better understand patterns. This research emphasizes the need for an approach in teaching that can enhance students' abstract thinking abilities and requires varied practice in determining numerical pattern problems.